Evaluation of Phytoextracts Against Curvularia Eragrostidis Causing Leaf Tip Blight of Spider Lilly in Vitro Condition - Prajapati, V. P.; Gajre, N. K.; Tandel, D. H.; Deshmukh, A. J.; Patel, R. C. (International Journal of Economic Plants, 2017)
The aqueous phytoextracts of commonly available ten plant species evaluated in vitro by poisoned food technique againsttheir inhibitory effect on the mycelial growth of Curvularia eragrostidis. The turmeric (Curcuma longa L.) was found most effective with per cent growth inhibition of 75.18% followed by dhatura (Datura metal L.)(46.67%), neem (Azardirachta indica A.Juss.) (44.07%), tulsi (Ocimum sanctum L.)(41.11%) and ardusi (Adhatoda vasica (L.) Nees.)(40.00%) for growth of Curvularia eragrostidis.